Immune Cells Combined With NLRP3 Inflammasome Inhibitor Exert Better Antitumor Effect on Pancreatic Ductal Adenocarcinoma - Liu, Hailiang; Xu, Yong; Liang, Kai; Liu, Rong (Frontiers in Oncology, 2020)
Pancreatic cancer is amongst the most aggressive malignancies associated with chronic inflammation. Moreover, cellular immunity can be inhibited by inflammation induced by NLRP3 inflammasome. Accordingly, NLRP3 inhibition combing CIK cells may improve anti-tumor efficacy. 3,4-methylenedioxy-β-nitrostyrene (MNS) was selected as a specific NLRP3 inflammasome inhibitor. Western Blot was used to evaluate the NLRP3 inflammasome expression in pancreatic cancer lines SW1990 and PANC-1. The impact of NLRP3 inhibition on migration, invasiveness and proliferation of pancreatic cancer cells were analyzed though wound healing assay, Transwell assay and CCK08 assay, respectively. The combing anti-tumor effect in vivo of CIK and NLRP3 inhibition was evaluated in a subcutaneous human pancreatic cancer Blab/c nudes model. Western Blot analysis showed significant expression of NLRP3 inflammasome in human pancreatic cancer lines SW1990 and PANC-1, and that MNS did significantly inhibit the expression of NLRP3 inflammasome in cell lines. Moreover, NLRP3 inhibition can significantly decrease the migration, invasiveness and proliferation of pancreatic cancer cells. In vivo experiments showed that combination treatment with MNS and CIK cells had greatest anti-tumor effect among four treatment groups including control, MNS and CIK. Combination treatment with NLRP3 inflammasome inhibition and CIK cells show greater anti-tumor efficacy though inflammation inhibition and of immunity restoration.